2021
DOI: 10.1007/s00586-021-06777-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a model to predict the probability of incurring a complication during spine surgery

Abstract: Purpose Predictive models in spine surgery are of use in shared decision-making. This study sought to develop multivariable models to predict the probability of general and surgical perioperative complications of spinal surgery for lumbar degenerative diseases. Methods Data came from EUROSPINE's Spine Tango Registry (1.2012–12.2017). Separate prediction models were built for surgical and general complications. Potential predictors included age, gender, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…However, we also found as important predictors certain specific clinical symptoms including motor deficit reported by the doctor, back pain and leg weakness as reported from the patient. These variables differ greatly from previous studies aiming to predict surgery complications which found the health insurance provider [13] or the ASA score (physical status score) as the best predictors [14].…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…However, we also found as important predictors certain specific clinical symptoms including motor deficit reported by the doctor, back pain and leg weakness as reported from the patient. These variables differ greatly from previous studies aiming to predict surgery complications which found the health insurance provider [13] or the ASA score (physical status score) as the best predictors [14].…”
Section: Discussioncontrasting
confidence: 70%
“…In a previous application of AI for a preoperative risk prediction model, a machine learning approach based on lasso logistic regression was used to predict complications after spinal surgery depending on patient variables with AUROC ranging from 0.7 to 0.76 [13]. Another regression model obtained similar results [14]. Machine learning models were also proposed to predict pain and functional outcomes after surgery [15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may involve surgical intervention at the same site, at a different site but due to the same condition, or repair of complications resulting from the initial surgical procedure [8]. Reoperation per se is strongly predictive of surgical complications in spinal surgery [9]. An additional burden of other health problems (multimorbidity) may carry an increased risk of surgical failure in DSD patients, including the need for reoperation.…”
Section: Introductionmentioning
confidence: 99%
“…When surgery is conducted near the spinal cord, complications will occur that could be very serious (Nasser et al, 2010). During spine surgery, the proximity of neural and vessel structures within the spinal cord requires high accuracy from surgeons (Zehnder et al, 2021). In patients with severe spinal deformity or congenital scoliosis, the spinal anatomy can be severely altered or extremely dysmorphic (Perez‐Machado et al, 2020).…”
Section: Introductionmentioning
confidence: 99%